If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(3/5)*y+2/5 = 4/5 // - 4/5
(3/5)*y+2/5-(4/5) = 0
(3/5)*y+2/5-4/5 = 0
3/5*y-2/5 = 0 // + 2/5
3/5*y = 2/5 // : 3/5
y = 2/5/3/5
y = 2/3
y = 2/3
| y=4x^2+40x+99 | | 48y^3+72y^2+27y= | | 8f+7q=3 | | 18=15-3(6t+5) | | 2x=4b+2a | | -4p+6q=46 | | 4x^2+36x+81= | | 8a+b-c-7a= | | -4j-(-5)/-7=13 | | -4=-2/5x | | 39/4*3 | | 4x-7(.03x)=79.59 | | 39/4x3 | | 4x=2x(3x-8) | | 21/3+11/4 | | x+(x+10)=150 | | (7x)/(59x+36)=(1)/(x) | | x^2-4x=19 | | .5*(4x-6)=11 | | -3x-2=-5 | | 3/5b-8=4 | | 11x=10x-18 | | x-(-19/14)=5/7 | | (6+2x)*5=10+(6x) | | 0.5*4x-6=11 | | fx=2x^2+6x-7 | | 5x+7-4=14 | | -20x+40-35x^2= | | 11(x-5)=-5-6 | | (6+2x)*5=13+(6x) | | X^3+x^2-7x-7=0 | | (6+2x)*5=13+6x |